Palliative Ventilator Withdrawal Practices in an Inpatient Hospice Unit. (July 2023) - Kaur, Ramandeep; Harmon, Elizabeth; Joseph, Augustin; Dhliwayo, Nyembezi L; Kramer, Neha; Chen, Elaine
Background: Palliative ventilator withdrawal (PVW) involves removal of mechanical ventilation in patients not expected to survive to allow a peaceful death. This process traditionally occurs in Intensive Care Units (ICU) and recently has evolved to occur in Inpatient Hospice and Palliative Care Units (IPU). Objectives: To describe the process and response of patients undergoing PVW in an IPU setting. Methods: This is a longitudinal observational cohort study of adult patients who underwent PVW in an IPU from January 2021 through March 2022. Results: Among 25 enrolled subjects, median age was 68 (IQR 62.5-76.5) years and 14 (56%) were females. Median time from PVW to death was 16.8 (IQR 2.6-100) hours. A registered nurse and attending physician were present in all the cases, while a respiratory therapist was present in 20 (80%) and chaplain in 9 (36%) of the cases. Before PVW, opioids and benzodiazepines were administered to 24 (96%) patients. Post PVW, respiratory distress was noted among 16 (64%) patients and medication was given to 15 (60%) patients for respiratory distress. There was a significant association between the presence of respiratory distress and administration of medication within 30 minutes after PVW ( P = .009). The rituals performed during PVW were reciting prayers for 11 (44%), playing music for 8 (32%), and observing silence for 6 (24%) of the patients. Conclusion: This study describes the PVW practices in an IPU setting where a multidisciplinary team was present during PVW for most of the cases and two-third of the patients undergoing PVW experienced respiratory distress immediately after PVW.